WEB MARKETPLACE DESIGN AND DEVELOPMENT FOR HOUSEHOLD NEEDS USING THE WDLC MODEL WITH THE SCRUM METHOD - Heru Wijayanto Aripradono; Muhammad Rivaldy Hisham (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
The fast digital era 4.0 revolution requires companies to be responsive in providing breakthroughs in their products so that they are able to guess consumer needs and distribute them in a short time. The growth of online shopping has brought about changes in the standardization of electronic commerce which affects business processes in various fields of business. The web can be used to retrieve data on products in the electronic market and one of them is household appliances which makes it easier for people to become sellers and buyers. The SCRUM method is a new continuous methodology in software development that is also widely used by other researchers because it is able to adapt to changes that occur during the development of the application process that is made. WDLC is a web-based application development method based on the adoption of SDLC that supports the creation of web applications, both simple and complex, and can be adapted to other methods, for example prototypes to be redeveloped repeatedly and gradually. The result of this applied research is a web marketplace for household needs that has been designed and developed using the SCRUM method with the WDLC model.